2014
DOI: 10.1002/nbm.3165
|View full text |Cite
|
Sign up to set email alerts
|

Inert fluorinated gas MRI: a new pulmonary imaging modality

Abstract: Fluorine-19 ((19)F) MRI of the lungs using inhaled inert fluorinated gases can potentially provide high quality images of the lungs that are similar in quality to those from hyperpolarized (HP) noble gas MRI. Inert fluorinated gases have the advantages of being nontoxic, abundant, and inexpensive compared with HP gases. Due to the high gyromagnetic ratio of (19)F, there is sufficient thermally polarized signal for imaging, and averaging within a single breath-hold is possible due to short longitudinal relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 65 publications
1
44
1
Order By: Relevance
“…We can now use the developed structured reporting method and comparative analysis to assess performance of these methods. In addition, MRI can be advantageous for lung function assessment when incorporating hyperpolarized and/or inert fluorinated gas MRI, which will be future areas of development in this model (Fain et al , 2007, Couch et al , 2014). …”
Section: Discussionmentioning
confidence: 99%
“…We can now use the developed structured reporting method and comparative analysis to assess performance of these methods. In addition, MRI can be advantageous for lung function assessment when incorporating hyperpolarized and/or inert fluorinated gas MRI, which will be future areas of development in this model (Fain et al , 2007, Couch et al , 2014). …”
Section: Discussionmentioning
confidence: 99%
“…MAGNETIC RESONANCE IMAGING (MRI) of the chest can provide regional assessment of lung ventilation by inhaling oxygen (O 2 ), hyperpolarized noble gases, or fluorinated gas . Oxygen‐enhanced (OE) MRI using a 3D radial ultrashort echo time (UTE) sequence supports quantitative differentiation of diseased vs. healthy lungs using whole lung ventilation defect percent (VDP) .…”
mentioning
confidence: 99%
“…An alternative to inhaled hyperpolarized gas contrast is inhaled fluorinated gas for both dynamic and static breathhold MRI measurements. While the relatively low SNR of 19 F gas MRI 132 has somewhat limited widespread development and use, a number of pioneering 19 F lung MRI clinical and preclinical dynamic studies, [133][134][135] as well as diffusionweighted studies, have demonstrated its utility and potential. 133 In future, hardware and pulse sequence advances will continue to increase 19 F MRI SNR, which will accelerate 19 F MRI morphological and morphometry measurements.…”
Section: Emerging Imaging Techniquesmentioning
confidence: 99%